Monitoring systematic control system for electrode usage at EDM section - Harun, Jannatunnaim (2013)
EDM is a CNC machine that uses electrical energy to erode the workpiece material, which takes the form opposite electrodes. The type of electrode made of electrically conductive material such as copper and graphite. The study was conducted at a metal fabrication company seeks to control the use of copper electrodes in the production process. Thus the purpose of this study is to increase the productivity of EDM section and supported by three objectives: (i) identify factors in the loss of EDM electrodes, (ii) the data recorded on the use of EDM electrodes, (iii) clarify the relationship between time and costs in terms of new electrode and reused. Observations and interviews were used to identify problems in EDM. Ishikawa diagrams were selected to analyze the factors that contribute to this problem. Check sheet was used to record the use of electrodes to show the difference between the use of new electrode and reusable electrodes. The results indicate that there is no systematic system for recording data for electrodes in EDM section. Results also show that the use of time and cost differences between new electrodes and electrode reusable high impact in terms of production costs and production time. In conclusion, a systematic control system on the EDM will provide more benefits in terms of reducing the time and cost of the product.